Gaya Kepemimpinan Wanita Pada Usaha Kecil Menengah di Tangerang Selatan - Sunarta Sunarta; Budi Permana Yusuf (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
This study aims to determine the management of women's leadership style to employee performance on home business. Building relationships with employees need experience in leading, Sources of development of the character of an entrepreneur also found in the family's internal education since childhood. The self-concept of an entrepreneur is a social product formed through the process of internalization and organization and psychological experiences. This psychological experience is the result of individual exploration of the environment and the reflection of himself received from others. Meet the needs of employees is a bond between leaders with subordinates to do, success is strongly influenced by internal and external environment, in the environment someone will be affected on psychological factors that are very supportive and influence the mindset of an entrepreneur, and have a desire to achieve a great job is also ready hard, diligent, have great confidence and perseverance in the fight. Leading patiently, with a sincere heart and always turning on two-way communication, has a successful self-concept and clear goal direction.